STRATEGI KEPALA SEKOLAH DALAM MENINGKATKAN MUTU SEKOLAH DAN KEDISIPLINAN GURU UPT SMP NEGERI 4 MATTIROBULU SATAP KABUPATEN PINRANG - Muhammad Arsyad Coke (Melati Institute, 2022)
The essence of leadership is following, namely the willingness of subordinates to follow the wishes of the leader. The principal acts as a central force that drives school life, understands his duties and functions for the success of the school and has a concern. The reality on the ground, the principal has not much improvised displaying his expertise. The assumption of the low quality of principals is caused by the non-transparent recruitment of principals, the lack of forums for improving the quality of principals, discipline and low motivation. The method used in this research is a qualitative approach. This type of research is descriptive qualitative, namely to understand the development of school quality and teacher discipline. The leadership strategy of the principal of UPT SMP Negeri 4 Mattirobulu Satap, Pinrang district in improving teacher performance, shows his leadership in a democratic style, is not rash in acting and making decisions, always deliberation. The strategy carried out by the principal in improving the quality of schools and teacher discipline is by fostering discipline, being a role model for teachers and students, holding seminars and training, collaborating with other educational institutions, bringing in experts, providing opportunities for teachers to supervise each other, provide and optimize educational facilities and equipment. Giving motivation to teachers, harmonious cooperation, involving teachers in every activity, trying to fulfill the wishes and needs of teachers in carrying out their duties, giving awards to teachers for improving school quality and teacher discipline, providing a sense of security at school, peaceful, applying the principle of kinship based on the intention of worship.